Public Swearing In Ceremony for Judges Charles Hamlin, Gene Gomes, Ralph Nunez, Mario Olmos and Victor Papadakis at Veterans' Memorial Auditorium - Watkins, Howard::::::::: (1983)
Judge Frank Creede, Jr., Rebecca Gomes and Judge Gene Gomes, Rachel Nunez and Judge Ralph Nunez and Mary Louise Frampton kissing Judge Mario Olmos Judges to right: John "Nip Gallagher", Buck Levis, Steven Vartabedian, James Aaron